2017 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2017
DOI: 10.1109/icassp.2017.7953062
|View full text |Cite
|
Sign up to set email alerts
|

Phase retrieval from STFT measurements via non-convex optimization

Abstract: The problem of recovering a signal from its phaseless short-time Fourier transform (STFT) measurements arises in several applications, such as ultra-short pulse measurements and ptychography. The redundancy offered by the STFT enables unique recovery under mild conditions. We show that in some cases, the principle eigenvector of a designed matrix recovers the underlying signal. This matrix is constructed as the solution of a simple least-squares problem. When these conditions are not met, we suggest to use thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…, where f d j is the j th Fourier vector in C d and γ ∈ R d has support [δ] produces an invertible system under a very mild condition. We further prove that this condition holds for almost all γ; this result is particularly interesting considering that γ ∈ C d has δ degrees of freedom, but must generate a spanning set for a subspace of dimension d(2δ − 1) when all shifts are taken in (7).…”
Section: Organization and Contributionsmentioning
confidence: 69%
See 2 more Smart Citations
“…, where f d j is the j th Fourier vector in C d and γ ∈ R d has support [δ] produces an invertible system under a very mild condition. We further prove that this condition holds for almost all γ; this result is particularly interesting considering that γ ∈ C d has δ degrees of freedom, but must generate a spanning set for a subspace of dimension d(2δ − 1) when all shifts are taken in (7).…”
Section: Organization and Contributionsmentioning
confidence: 69%
“…Among the first treatments of local measurements are [7,20,33], in which it is shown that STFT (short-time Fourier transform [2,48]) measurements with specific properties can allow (sparse) phase retrieval in the noiseless setting, and several recovery methods have been proposed [9,27]. Similarly, the phase retrieval approach from [1] was extended to STFT measurements in [53] in order to produce recovery guarantees in the noiseless setting.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In this generation process of image data, time series from tests are transformed into frequency spectrums by using short-time Fourier transform (STFT). For an original discrete signal sequence x(n), a pre-determined window function is used to divide the time series into many segments, and it is assumed the signal is pseudo-stationary over a short interval, and then Fourier transform is carried out on each window length (Bendory et al, 2017;Rashid and Louis, 2020). The transform process of STFT is shown in Figure 3.…”
Section: Generation Of Spectrum Image Datamentioning
confidence: 99%
“…Then we apply Algorithm 1 to search for the solution of (13). In Algorithm 1, λ is the step size calculated by the backtracking method which can be seen in Algorithm 2.…”
Section: Algorithm For the Phase Retrieval With Background Informationmentioning
confidence: 99%